Self-Sustained Regulation or Self-Perpetuating Dysregulation: ROS-dependent HIF-YAP-Notch Signaling as a Double-Edged Sword on Stem Cell Physiology and Tumorigenesis - Guo, Chin-Lin (Frontiers in Cell and Developmental Biology, 2022)
Organ development, homeostasis, and repair often rely on bidirectional, self-organized cell-niche interactions, through which cells select cell fate, such as stem cell self-renewal and differentiation. The niche contains multiplexed chemical and mechanical factors. How cells interpret niche structural information such as the 3-D topology of organs and integrate with multiplexed mechano-chemical signals is an open active research field. Among all the niche factors, reactive oxygen species (ROS) have recently gained growing interest. Once considered harmful, ROS are now recognized as an important niche factor in the regulation of tissue mechanics and topology through, e.g., the HIF-YAP-Notch signaling pathways. These pathways are not only involved in the regulation of stem cell physiology but also associated with inflammation, neurological disorder, aging, and tumorigenesis. Positive feedback circuits have been identified in the interplay of ROS and HIF-YAP-Notch signaling, leading to a possibility that under aberrant conditions, self-organized, ROS-dependent physiological regulations can be switched to self-perpetuating dysregulation, making ROS a double-edged sword at the interface of stem cell physiology and tumorigenesis. In this review, we discuss the recent findings on how ROS and tissue mechanics affect YAP-HIF-Notch signaling, and how ROS-YAP-HIF-Notch signaling regulates the immune checkpoint molecule PD-L1.